Function over form: The benefits of aspen as surrogate brood‐rearing habitat for greater sage‐grouse - Michel T. Kohl; Charles P. Sandford; Paul C. Rogers; Renee Chi; Terry A. Messmer; David K. Dahlgren (Ecosphere)
Abstract Species of conservation concern are often habitat specialists, posing significant risk to those species when specific plant communities are threatened. As a result, practitioners habitually focus conservation efforts on these communities while ignoring ecological mechanisms that explain the wildlife–plant relationships. In doing so, practitioners may overlook alternative vegetation communities that could maintain wildlife populations under alternative conditions (e.g., climate change). Here, we term these areas surrogate habitat, defined as vegetation communities or resource sites that provide similar critical resources as conventional sites, and assess their potential for conservation using a case study of greater sage‐grouse (Centrocercus urophasianus) on Parker Mountain, Utah (1998–2009). Sage‐grouse are a sagebrush‐obligate species and a species of conservation concern. Range‐wide conservation efforts have long emphasized management of seasonal habitats within semiarid sagebrush ecosystems, specifically management of mesic or wet meadow sites that provide brood‐rearing habitat required for population persistence. Despite this requirement, no conventional mesic habitat exists on Parker Mountain, yet it supports one of Utah's largest sage‐grouse populations. Rather, the Parker sagebrush system abuts quaking aspen (Populus tremuloides) stands that may provide brood‐rearing habitat analogous to wet meadow sites. It is unclear, however, to what extent sage‐grouse use these aspen stands because sage‐grouse commonly avoid tall structures (e.g., trees) and their associated avian predators. Thus, we tested whether (1) sage‐grouse selected for surrogate habitat (i.e., aspen edge) and (2) selection behaviors related to surrogate habitat had demographic effects on the population. As we predicted, sage‐grouse selected for these areas, and the sage‐grouse that spent increased time closer to aspen edges did not experience increased mortality. Together, this demonstrates that the aspen–sagebrush edge provided a surrogate for the wet meadows used by other populations. More broadly, this suggests that conservation practitioners should move beyond simplistic wildlife–habitat associations toward a more holistic view of animal ecology focused on the wildlife–resource association, an approach that becomes particularly useful in areas where conventional obligate habitat may be degraded or lost. This work also implores us to examine alternative habitat potential rather than applying one‐size‐fits‐all models to threatened species conservation.